Vacuum arc-extinguishing chamber based on carbon-carbon composite material heat dissipation coating and manufacturing method
By applying a carbon-carbon composite heat dissipation coating with high thermal conductivity and high emissivity inside the vacuum arc extinguishing chamber, the problem of low heat dissipation efficiency of the vacuum arc extinguishing chamber is solved, and the heat dissipation efficiency and service life of the equipment are improved.
Patent Information
- Application Number
- CN202411357823.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The heat generated by the vacuum arc extinguishing chamber when the high voltage current is cut off is difficult to effectively dissipate heat, which affects the safety and reliability of the equipment and service life.
The shell, shielding cover, inner wall of the static end cap and inner wall of the moving end cap of the vacuum arc extinguishing chamber are coated with a high thermal conductivity and high emissivity carbon-carbon composite heat dissipation coating, which accelerates heat dissipation through conduction and radiant heat dissipation.
It significantly improves the heat dissipation efficiency of the vacuum arc extinguishing chamber, extends the service life of the equipment, and maintains the stable performance of the coating under high temperature environments.
Smart Images

Figure CN119153263A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vacuum interrupter chambers, and in particular to a vacuum interrupter chamber based on a carbon-carbon composite material heat dissipation coating and a manufacturing method thereof. Background Art
[0002] The vacuum interrupter, also known as the vacuum switch tube, is the core component of the medium and high voltage power switch. Its main function is to quickly extinguish the arc and suppress the current after the medium and high voltage circuit is cut off from the power supply through the excellent insulation of the vacuum in the tube, so as to avoid accidents and unexpected events. During the process of breaking the short-circuit current by the vacuum interrupter, a large amount of heat is released. How to dissipate this heat quickly is not only related to the service life of the contact, but also to the safety and reliability of the vacuum interrupter.
[0003] Currently, the well-known heat dissipation methods include conduction heat dissipation, convection heat dissipation, radiation heat dissipation, etc. Since the vacuum interrupter is in a vacuum environment, there is basically no convection air, and the internal convection heat dissipation is limited, and heat dissipation can only be carried out outdoors. At present, the heat dissipation in the vacuum interrupter mainly relies on radiation heat dissipation and conduction heat dissipation, but the effect is not obvious. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a vacuum arc extinguishing chamber based on a carbon-carbon composite material heat dissipation coating and a manufacturing method thereof.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a vacuum arc chamber based on a carbon-carbon composite material heat dissipation coating, wherein the inner wall of the shell, the outer wall of the shielding cover, the inner wall of the static end cover and the inner wall of the dynamic end cover of the vacuum arc chamber are coated with a carbon-carbon composite material heat dissipation coating.
[0007] Preferably, the carbon-carbon composite heat dissipation coating has a thickness of 100-300 μm.
[0008] Preferably, the structure of the vacuum arc chamber includes a static end cover, a vacuum arc chamber shell, a static end conductive rod, a shielding cover, a static end electrode contact, a static end electrode contact sheet, a moving end electrode contact sheet, a moving end electrode contact, a moving end conductive rod, a bellows, and a moving end cover.
[0009] Preferably, the raw materials for preparing the carbon-carbon composite material heat dissipation coating include: carbon-carbon composite material, resin, curing agent, leveling agent, defoaming agent and talcum powder; the content of carbon-carbon composite material in the carbon-carbon composite material heat dissipation coating is 20-50wt%; further preferably, the resin includes one of polyimide resin and silicone resin; in some specific embodiments of the present invention, the curing agent is a polyamide curing agent.
[0010] Further preferably, the raw materials for preparing the carbon-carbon composite heat dissipation coating include: 10-20wt% resin, 10-15wt% curing agent, 10-15wt% leveling agent, 10-15wt% defoaming agent, 10-15wt% talcum powder, 20-50wt% carbon-carbon composite material, and the mass fractions of the six raw materials can be appropriately varied within the above range, and they only need to be added together to be 100wt%.
[0011] Preferably, the carbon-carbon composite material of the present invention comprises a matrix and a reinforcement material, and the mass ratio of the reinforcement to the matrix is (2-3): (3-7). The raw material of the reinforcement is polyacrylonitrile, and the raw material of the matrix is asphalt or resin or alkane, alkene, hydrocarbon gas.
[0012] Preferably, the method for preparing the carbon-carbon composite heat dissipation coating comprises the following steps: mixing the carbon-carbon composite material, resin, curing agent, leveling agent, defoaming agent and talcum powder, extruding them using an extruder, and then tableting them, cooling them to obtain flakes; and crushing and sieving the flakes.
[0013] Preferably, the carbon-carbon composite material is prepared by a preparation method comprising the following steps:
[0014] (1) adding polyacrylonitrile to a solvent and stirring to obtain a spinning solution, then placing the spinning solution in nitrogen vapor, the solvent is evaporated and recovered in a condenser to form primary fibers; after the primary fibers are shaped, nano-carbon fibers are added for ultrasonic mixing to obtain a reinforcement, i.e., a carbon fiber preform;
[0015] (2) densifying the carbon fiber preform by vacuum liquid phase impregnation of the matrix or chemical vapor deposition of the matrix;
[0016] (3) graphitizing the densified material to obtain the carbon-carbon composite material;
[0017] The mass ratio of the reinforcement to the matrix is (2-3): (3-7); the raw material of the matrix is one of asphalt, resin or carbon source gas. The carbon source gas includes alkane and olefin gases.
[0018] Further preferably, in step (1), the content of nano-carbon fibers in the carbon fiber preform is 5-15 wt %.
[0019] Further preferably, the vacuum liquid phase impregnation matrix includes the following steps: pouring molten thermosetting resin or thermoplastic asphalt into a container containing a reinforcement for vacuum impregnation; filtering using filter paper, and the impregnation and filtration process is performed 1-4 times; then hot isostatic pressing; and finally carbonizing in an inert gas.
[0020] Further preferably, the conditions for the vacuum impregnation of the substrate are temperature 70-90°C, vacuum, and time 1-3h; the conditions for the hot isostatic pressing are time 2-10h, temperature 500-750°C, vacuum, and pressure 90-110MPa; the carbonization is: carbonization in Ar gas at 950-1050°C and 90-110MPa for 2-10h, and then carbonization in He gas at 1350-1450°C and 90-110MPa for 2-10h.
[0021] Further preferably, the chemical vapor deposition substrate comprises the following steps:
[0022] The carbon fiber preform is placed in a carbon source gas for chemical vapor deposition treatment at a temperature of 800-1200° C. for 50-100 hours; the treatment is performed 1-4 times in total.
[0023] Further preferably, the graphitization treatment step is: placing the densified material in a heating device at a temperature of 2000-3000° C. for 2-10 hours; the graphitization treatment step is performed 1-7 times in total.
[0024] The second aspect of the present invention provides a method for preparing a vacuum interrupter based on a carbon-carbon composite material heat dissipation coating, comprising the following steps:
[0025] 1) Pre-treat the workpiece surface of the vacuum interrupter;
[0026] 2) Cleaning the pre-treated vacuum interrupter workpiece;
[0027] 3) Spray the carbon-carbon composite material heat dissipation coating on the vacuum interrupter workpiece that needs to be sprayed, and heat and cure;
[0028] 4) Assembling the various workpieces of the vacuum interrupter into a whole piece, and then adjusting the vacuum degree inside the vacuum interrupter with a vacuum pump to obtain the vacuum interrupter based on the carbon-carbon composite material heat dissipation coating.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The invention accelerates the conduction heat dissipation and radiation heat dissipation in the vacuum interrupter and improves the heat dissipation efficiency of the vacuum interrupter by coating a heat dissipation coating with high thermal conductivity and high emissivity in the vacuum interrupter.
[0031] The carbon-carbon composite heat dissipation coating of the present invention is uniform, has good adhesion, can remain stable in a high temperature environment, and does not decay in performance. By applying the heat dissipation coating, the conduction heat dissipation and radiation heat dissipation inside the vacuum interrupter are accelerated, the heat dissipation efficiency of the vacuum interrupter is improved, and the service life of the vacuum interrupter is increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the structure of a vacuum interrupter based on a carbon-carbon composite heat dissipation coating;
[0033] Figure 2 A half-section diagram of the vacuum interrupter and a schematic diagram of the location of the heat dissipation coating;
[0034] Figure 3 Create a flow chart for carbon-carbon composite heat dissipation coating;
[0035] Figure 4 Create a flow chart for vacuum interrupter based on carbon-carbon composite heat dissipation coating;
[0036] In the attached figure: 01-static end cover, 02-vacuum arc extinguishing chamber shell, 03-static end conductive rod, 04-shielding cover, 05-static end electrode contact, 06-static end electrode contact sheet, 07-moving end electrode contact sheet, 08-moving end electrode contact, 09-moving end conductive rod, 10-bellows, 11-moving end cover, 12-carbon-carbon composite material heat dissipation coating. DETAILED DESCRIPTION
[0037] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0039] As attached Figure 1 As shown, the structure of the vacuum interrupter based on the carbon-carbon composite material heat dissipation coating of the present invention includes: a static end cover 01, a vacuum interrupter housing 02, a static end conductive rod 03, a shielding cover 04, a static end electrode contact 05, a static end electrode contact sheet 06, a moving end electrode contact sheet 07, a moving end electrode contact 08, a moving end conductive rod 09, a bellows 10, a moving end cover 11 and a carbon-carbon composite material heat dissipation coating 12; the coating parts of the carbon-carbon composite material heat dissipation coating 12 include the inner wall of the vacuum interrupter housing 02, the outer wall of the shielding cover 04, the inner wall of the static end cover 01 and the inner wall of the moving end cover 11.
[0040] The present invention provides a method for manufacturing a vacuum interrupter based on a carbon-carbon composite material heat dissipation coating, comprising the following steps:
[0041] (1) Pre-treating the workpiece surface of the vacuum interrupter;
[0042] (2) Cleaning the pre-treated vacuum interrupter workpiece;
[0043] (3) using an electrostatic spraying process to spray a carbon-carbon composite heat dissipation coating onto a vacuum interrupter workpiece, and heating and curing the carbon-carbon composite heat dissipation coating at a temperature of 150-200° C. for 10-30 min to form the carbon-carbon composite heat dissipation coating;
[0044] (4) Assembling the vacuum arc chamber workpiece into a whole piece, and then adjusting the vacuum degree inside the vacuum arc chamber with a vacuum pump to obtain a carbon-carbon composite material heat dissipation coating vacuum arc chamber.
[0045] In step (1), the pretreatment is sandblasting pretreatment, and the surface of the vacuum interrupter workpiece is polished and deburred. After acceptance, step (2) is performed.
[0046] In step (2), the cleaning process is specifically as follows: soak the pre-treated vacuum interrupter workpiece and then perform ultrasonic cleaning, then rinse it with clean water and then perform dehydration treatment, and then dry it; after acceptance, proceed to step (3).
[0047] The carbon-carbon composite material in the carbon-carbon composite material heat dissipation coating of the present invention comprises a matrix and a reinforcing material, and the mass ratio of the reinforcing material to the matrix is (2-3): (3-7). The raw material of the reinforcing material is polyacrylonitrile, and the raw material of the matrix is asphalt or resin or alkane, alkene, hydrocarbon gas.
[0048] like Figure 3 As shown, the preparation method of the carbon-carbon composite heat dissipation coating of the present invention is as follows:
[0049] S1, adding polyacrylonitrile to a solvent and stirring to obtain a spinning solution, then placing the spinning solution in nitrogen vapor, the solvent is evaporated and recovered in a condenser to form primary fibers; after the primary fibers are shaped, nano-carbon fibers are added for ultrasonic mixing to obtain a reinforcement, i.e., a carbon fiber preform;
[0050] S2, preform densification, the densification includes two methods: vacuum liquid phase impregnation and vacuum vapor deposition. The liquid phase impregnation, 80 ° C, 2 hours of drying process to remove the gas and moisture in the pores of the reinforcement. By pouring the melted thermosetting resin (phenolic resin, epoxy resin, polyimide resin, acetylene resin, any one or a combination of at least two) or thermoplastic asphalt (coal tar pitch or petroleum asphalt) into the tray containing the reinforcement for vacuum impregnation. The conditions of vacuum impregnation are temperature 80 ° C, vacuum, and time 2 hours. Filtering is performed using 1μm filter paper, and the filtering conditions are temperature 80 ° C, vacuum, and time 24 hours. The process of impregnation and filtration is cycled 1-4 times. Hot isostatic pressing is performed at a temperature of 500-750 ° C, vacuum, and pressure of 100MPa for 2-10h. Subsequently, carbonization is performed at 1000 ° C and 100MPa in Ar gas for 2-10h, and then carbonization is performed at 1400 ° C and 100MPa in He gas for 2-10h. The chemical vapor deposition is to place the carbon fiber preform in an alkane, alkene, or hydrocarbon carbon source gas for chemical vapor deposition at a temperature of 800-1200° C. for 50 h to 100 h. Repeat 1-4 times to obtain a carbon-carbon composite material sample;
[0051] S3, performing pressureless graphitization treatment at a temperature of 2000-3000°C for 2-10 hours to obtain a carbon-carbon composite material. Repeating S3 treatment 1-7 times to obtain a finished carbon-carbon composite material;
[0052] S4, crushing and sieving the carbon-carbon composite material product obtained in S3 to obtain carbon-carbon mixed material particles, adding polyimide resin or silicone resin, polyamide curing agent, leveling agent, defoaming agent and talcum powder to a mixer to obtain a mixture, wherein the carbon-carbon composite material content in the mixture is 20-50%;
[0053] S5, pouring the mixed material in S4 into a twin-screw extruder to melt and extrude, the screw speed is 20-100 Hz, the melting temperature is 80-140° C., and then passing through a roller press to sheet, and cooling to obtain a sheet;
[0054] S6, crushing the flakes, sieving, and obtaining a carbon-carbon composite material heat dissipation powder coating with a particle size of 0-50 μm.
[0055] Example 1
[0056] This embodiment provides a method for manufacturing a vacuum interrupter based on a carbon-carbon composite heat dissipation coating, comprising the following steps:
[0057] (1) Pre-treating the workpiece surface of the vacuum interrupter;
[0058] (2) Cleaning the pre-treated vacuum interrupter workpiece;
[0059] (3) using an electrostatic spraying process to spray a carbon-carbon composite heat dissipation coating onto a vacuum interrupter workpiece, and heating and curing the carbon-carbon composite heat dissipation coating at a temperature of 200° C. for 30 min to form the carbon-carbon composite heat dissipation coating;
[0060] (4) Assembling the vacuum arc chamber workpiece into a whole piece, and then adjusting the vacuum degree inside the vacuum arc chamber with a vacuum pump to obtain a carbon-carbon composite material heat dissipation coating vacuum arc chamber.
[0061] In step (1), the pretreatment is sandblasting pretreatment, and the surface of the vacuum interrupter workpiece is polished and deburred. After acceptance, step (2) is performed.
[0062] In step (2), the cleaning process is specifically as follows: soak the pre-treated vacuum interrupter workpiece and then perform ultrasonic cleaning, then rinse it with clean water and then perform dehydration treatment, and then dry it; after acceptance, proceed to step (3).
[0063] In step (3), the thickness of the carbon-carbon composite heat dissipation coating is 300 μm.
[0064] In step (3), the preparation method of the carbon-carbon composite heat dissipation coating is as follows:
[0065] S1, slowly add polyacrylonitrile powder to the stirred dimethylformamide solution, and continuously stir at room temperature until it is completely dissolved to obtain a clear and transparent spinning solution, in which the polyacrylonitrile concentration is 15%. The spinning solution is placed in 50°C nitrogen vapor, the solvent is evaporated and recovered in the condenser to form primary fibers. These fibers are washed and dried five times, shaped at 170°C, and then 10% nano-carbon fibers are added for ultrasonic mixing to finally obtain a reinforcement, i.e., a carbon fiber preform;
[0066] S2, liquid phase impregnation, 80℃, 2 hours drying process to remove gas and moisture in the pores of the reinforcement. By removing gas and moisture, the density and interlaminar shear strength are increased. The molten phenolic resin is poured into a tray containing the reinforcement for vacuum impregnation, and the mass ratio of the reinforcement to the phenolic acid resin is 2:3. The conditions for vacuum impregnation are temperature 80℃, vacuum, and time 2 hours. 1μm filter paper is used for filtration, and the filtration conditions are temperature 80℃, vacuum, and time 24 hours. The impregnation and filtration process is cycled 4 times. Hot isostatic pressing at a temperature of 750℃, vacuum, and pressure of 100MPa for 10h can increase the carbon yield. Subsequently, it is carbonized at 1000℃ and 100MPa in Ar gas for 10h, and then carbonized at 1400℃ and 100MPa in He gas for 10h. The secondary carbonization makes the carbon-carbon composite material have a higher density.
[0067] S3, performing pressureless graphitization treatment at a temperature of 3000° C. for 10 h to obtain a carbon-carbon composite material. Repeating S3 treatment 7 times to obtain a finished carbon-carbon composite material.
[0068] S4, crushing and sieving the carbon-carbon composite material product obtained in S3 to obtain a carbon-carbon composite material, preparing an additive from 20% polyimide resin or silicone resin, 15% polyamide curing agent, 15% leveling agent, 10% defoaming agent and 10% talcum powder, adding the additive to a mixer together with the carbon-carbon composite material to obtain a mixture, wherein the carbon-carbon composite material content in the mixture is 30%;
[0069] S5, pouring the mixed material in S4 into a twin-screw extruder, extruding after melting, the screw speed is 50 Hz, the melting temperature is 140° C., and then pressing through a roller press to obtain a sheet, and cooling to obtain a sheet;
[0070] S6, crushing the flakes, sieving, and obtaining a carbon-carbon composite material heat dissipation powder coating with a particle size of 0-50 μm.
[0071] Example 2
[0072] This embodiment provides a method for manufacturing a vacuum interrupter based on a carbon-carbon composite heat dissipation coating, comprising the following steps:
[0073] (1) Pre-treating the workpiece surface of the vacuum interrupter;
[0074] (2) Cleaning the pre-treated vacuum interrupter workpiece;
[0075] (3) using an electrostatic spraying process to spray a carbon-carbon composite heat dissipation coating onto a vacuum interrupter workpiece, and heating and curing the carbon-carbon composite heat dissipation coating at a temperature of 200° C. for 20 min to form the carbon-carbon composite heat dissipation coating;
[0076] (4) Assembling the vacuum arc chamber workpiece into a whole piece, and then adjusting the vacuum degree inside the vacuum arc chamber with a vacuum pump to obtain a carbon-carbon composite material heat dissipation coating vacuum arc chamber.
[0077] In step (1), the pretreatment is sandblasting pretreatment, and the surface of the vacuum interrupter workpiece is polished and deburred. After acceptance, step (2) is performed.
[0078] In step (2), the cleaning process is specifically as follows: soak the pre-treated vacuum interrupter workpiece and then perform ultrasonic cleaning, then rinse it with clean water and then perform dehydration treatment, and then dry it; after acceptance, proceed to step (3).
[0079] In step (3), the thickness of the carbon-carbon composite heat dissipation coating is 300 μm.
[0080] In step (3), the preparation method of the carbon-carbon composite heat dissipation coating is as follows:
[0081] S1, slowly add polyacrylonitrile powder to the stirred dimethylformamide solution, and continuously stir at room temperature until it is completely dissolved to obtain a clear and transparent spinning solution, in which the polyacrylonitrile concentration is 15%. The spinning solution is placed in 50°C nitrogen vapor, the solvent is evaporated and recovered in the condenser to form primary fibers. These fibers are washed and dried five times, shaped at 170°C, and then 10% nano-carbon fibers are added for ultrasonic mixing to finally obtain a reinforcement, i.e., a carbon fiber preform;
[0082] S2, liquid phase impregnation, 80℃, 2 hours drying process to remove gas and moisture in the pores of the reinforcement. Vacuum impregnation is performed by pouring molten petroleum asphalt into a tray containing reinforcement, and the mass ratio of reinforcement to petroleum asphalt is 2:3. The conditions for vacuum impregnation are temperature 80℃, vacuum, and time 2 hours. Filtration is performed using 1μm filter paper, and the filtration conditions are temperature 80℃, vacuum, and time 24 hours. The impregnation and filtration process is cycled 4 times. Hot isostatic pressing is performed at a temperature of 750℃, vacuum, and pressure of 100MPa for 10h. Subsequently, carbonization is performed at 1000℃ and 100MPa in Ar gas for 10h, and then carbonization is performed at 1400℃ and 100MPa in He gas for 10h;
[0083] S3, performing pressureless graphitization treatment at a temperature of 2000°C for 10 hours to obtain a carbon-carbon composite material. Repeat S3 treatment 7 times to obtain a finished carbon-carbon composite material;
[0084] S4, crushing and sieving the carbon-carbon composite material product obtained in S3 to obtain a carbon-carbon composite material, preparing an additive from 10% polyimide resin or silicone resin, 10% polyamide curing agent, 10% leveling agent, 10% defoaming agent and 10% talcum powder, adding the additive to a mixer together with the carbon-carbon composite material to obtain a mixture, wherein the carbon-carbon composite material content in the mixture is 50%;
[0085] S5, pouring the mixed material in S4 into a twin-screw extruder, extruding after melting, the screw speed is 50 Hz, the melting temperature is 140° C., and then pressing through a roller press to obtain a sheet, and cooling to obtain a sheet;
[0086] S6, crushing the flakes, sieving, and obtaining a carbon-carbon composite material heat dissipation powder coating with a particle size of 0-50 μm.
[0087] Example 3
[0088] This embodiment provides a method for manufacturing a vacuum interrupter based on a carbon-carbon composite heat dissipation coating, comprising the following steps:
[0089] (1) Pre-treating the workpiece surface of the vacuum interrupter;
[0090] (2) Cleaning the pre-treated vacuum interrupter workpiece;
[0091] (3) using an electrostatic spraying process to spray a carbon-carbon composite heat dissipation coating onto a vacuum interrupter workpiece, and heating and curing the carbon-carbon composite heat dissipation coating at a temperature of 200° C. for 30 min to form the carbon-carbon composite heat dissipation coating;
[0092] (4) Assembling the vacuum arc chamber workpiece into a whole piece, and then adjusting the vacuum degree inside the vacuum arc chamber with a vacuum pump to obtain a carbon-carbon composite material heat dissipation coating vacuum arc chamber.
[0093] In step (1), the pretreatment is sandblasting pretreatment, and the surface of the vacuum interrupter workpiece is polished and deburred. After acceptance, step (2) is performed.
[0094] In step (2), the cleaning process is specifically as follows: soak the pre-treated vacuum interrupter workpiece and then perform ultrasonic cleaning, then rinse it with clean water and then perform dehydration treatment, and then dry it; after acceptance, proceed to step (3).
[0095] In step (3), the thickness of the carbon-carbon composite heat dissipation coating is 300 μm.
[0096] In step (3), the preparation method of the carbon-carbon composite heat dissipation coating is as follows:
[0097] S1, slowly add polyacrylonitrile powder to the stirred dimethylformamide solution, and continuously stir at room temperature until it is completely dissolved to obtain a clear and transparent spinning solution, in which the polyacrylonitrile concentration is 15%. The spinning solution is placed in 50°C nitrogen vapor, the solvent is evaporated and recovered in the condenser to form primary fibers. These fibers are washed and dried five times, shaped at 170°C, and then 10% nano-carbon fibers are added for ultrasonic mixing to finally obtain a reinforcement, i.e., a carbon fiber preform;
[0098] S2, chemical vapor deposition, placing the carbon fiber preform in ethane gas for chemical vapor deposition treatment, the mass ratio of reinforcement to ethane is 2:3, the temperature is 1200℃, and the time is 100h. Repeat 4 times to obtain a carbon-carbon composite material sample;
[0099] S3, performing pressureless graphitization treatment at a temperature of 3000°C for 10 hours to obtain a carbon-carbon composite material. Repeating S3 treatment 7 times to obtain a finished carbon-carbon composite material;
[0100] S4, crushing and sieving the carbon-carbon composite material product obtained in S3 to obtain a carbon-carbon composite material, preparing an additive from 10% polyimide resin or silicone resin, 10% polyamide curing agent, 10% leveling agent, 10% defoaming agent and 10% talcum powder, adding the additive to a mixer together with the carbon-carbon composite material to obtain a mixture, wherein the carbon-carbon composite material content in the mixture is 50%;
[0101] S5, pouring the mixed material in S4 into a twin-screw extruder, extruding after melting, the screw speed is 50 Hz, the melting temperature is 140° C., and then pressing through a roller press to obtain a sheet, and cooling to obtain a sheet;
[0102] S6, crushing the flakes, sieving, and obtaining a carbon-carbon composite material heat dissipation powder coating with a particle size of 0-50 μm.
[0103] Comparative Example 1
[0104] The implementation steps are the same as those in Example 1, the only difference being that the coating thickness of the carbon-carbon composite heat dissipation coating is 200 μm.
[0105] Comparative Example 2
[0106] The implementation steps are the same as those in Example 2, with the only difference being that when preparing the carbon-carbon composite heat dissipation coating, the pressureless graphitization treatment at 2000° C. and 10 h in step S3 is repeated 7 times instead of 3 times.
[0107] Comparative Example 3
[0108] The implementation steps are the same as those of Example 3, with the only difference being that in step S2 when preparing the carbon-carbon composite heat dissipation coating, the chemical vapor deposition step is repeated once instead of four times.
[0109] Performance Testing
[0110] The vacuum interrupter chamber of the carbon-carbon composite heat dissipation coating described in the embodiment and the comparative embodiment was tested for coating reflectivity, coating emissivity and equipment cooling effect. The test results are shown in Table 1.
[0111] Table 1 Coating performance and vacuum interrupter heat dissipation test results
[0112] Thermal conductivity (W / (m·K) Reflectivity Emissivity Heat dissipation effect(℃) Example 1 5200 0.93 0.92 12.5 Example 2 5160 0.91 0.89 11.8 Example 3 5050 0.90 0.89 11.4 Comparative Example 1 4900 0.88 0.87 11.2 Comparative Example 2 4860 0.89 0.88 10.9 Comparative Example 3 4850 0.82 0.83 9.2
[0113] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A vacuum interrupter based on a carbon-carbon composite heat dissipation coating, characterized in that: The inner wall of the shell, the outer wall of the shielding cover, the inner wall of the static end cover and the inner wall of the dynamic end cover of the vacuum interrupter are coated with a carbon-carbon composite material heat dissipation coating.
2. The vacuum interrupter based on the carbon-carbon composite material heat dissipation coating according to claim 1, characterized in that: The structure of the vacuum interrupter includes a static end cover, a vacuum interrupter shell, a static end conductive rod, a shielding cover, a static end electrode contact, a static end electrode contact sheet, a dynamic end electrode contact sheet, a dynamic end electrode contact, a dynamic end conductive rod, a bellows, and a dynamic end cover.
3. The vacuum interrupter based on the carbon-carbon composite heat dissipation coating according to claim 1 or 2, characterized in that: The raw materials for preparing the carbon-carbon composite heat dissipation coating include: carbon-carbon composite material, resin, curing agent, leveling agent, defoaming agent and talcum powder; the content of the carbon-carbon composite material in the carbon-carbon composite heat dissipation coating is 20-50wt%.
4. The vacuum interrupter based on the carbon-carbon composite material heat dissipation coating according to claim 3, characterized in that: The preparation method of the carbon-carbon composite heat dissipation coating comprises the following steps: mixing the carbon-carbon composite material, resin, curing agent, leveling agent, defoaming agent and talcum powder, extruding them by an extruder, pressing them into sheets, and cooling them to obtain sheets; and crushing and sieving the sheets.
5. The vacuum interrupter based on the carbon-carbon composite material heat dissipation coating according to claim 3, characterized in that: The carbon-carbon composite material is prepared by a preparation method comprising the following steps: (1) adding polyacrylonitrile to a solvent and stirring to obtain a spinning solution, then placing the spinning solution in nitrogen vapor, the solvent is evaporated and recovered in a condenser to form primary fibers; after the primary fibers are shaped, nano-carbon fibers are added for ultrasonic mixing to obtain a reinforcement, i.e., a carbon fiber preform; (2) densifying the carbon fiber preform by vacuum liquid phase impregnation of the matrix or chemical vapor deposition of the matrix; (3) graphitizing the densified material to obtain the carbon-carbon composite material; The mass ratio of the reinforcement to the matrix is (2-3):(3-7); the raw material of the matrix is one of asphalt, resin or carbon source gas.
6. The vacuum interrupter based on the carbon-carbon composite heat dissipation coating according to claim 5, characterized in that: The vacuum liquid phase impregnation matrix comprises the following steps: pouring molten thermosetting resin or thermoplastic asphalt into a container containing a reinforcement body for vacuum impregnation; filtering using filter paper, and the impregnation and filtering process is performed 1-4 times; then hot isostatic pressing; and finally carbonizing in an inert gas.
7. The vacuum interrupter based on the carbon-carbon composite material heat dissipation coating according to claim 6, characterized in that: The conditions for the vacuum impregnation of the substrate are temperature 70-90°C, vacuum, and time 1-3h; the conditions for the hot isostatic pressing are time 2-10h, temperature 500-750°C, vacuum, and pressure 90-110MPa; the carbonization is: carbonization in Ar gas at 950-1050°C and 90-110MPa for 2-10h, and then carbonization in He gas at 1350-1450°C and 90-110MPa for 2-10h.
8. The vacuum interrupter based on the carbon-carbon composite heat dissipation coating according to claim 5, characterized in that: The chemical vapor deposition substrate comprises the following steps: The carbon fiber preform is placed in a carbon source gas for chemical vapor deposition treatment at a temperature of 800-1200° C. for 50-100 hours; the treatment is performed 1-4 times in total.
9. The vacuum interrupter based on the carbon-carbon composite material heat dissipation coating according to claim 5, characterized in that: The graphitization treatment step is: placing the densified material in a heating device at a temperature of 2000-3000° C. for 2-10 hours; the graphitization treatment step is performed 1-7 times in total.
10. A method for preparing a vacuum interrupter based on a carbon-carbon composite heat dissipation coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Pre-treat the workpiece surface of the vacuum interrupter; 2) Cleaning the pre-treated vacuum interrupter workpiece; 3) Spray the carbon-carbon composite material heat dissipation coating on the vacuum interrupter workpiece that needs to be sprayed, and heat and cure; 4) Assembling the various workpieces of the vacuum interrupter into a whole piece, and then adjusting the vacuum degree inside the vacuum interrupter with a vacuum pump to obtain the vacuum interrupter based on the carbon-carbon composite material heat dissipation coating.
Citation Information
Patent Citations
Method for machining polyacrylonitrile pre-oxidized fiber reinforced composite material bearing
CN108249945A
Vacuum arc-extinguishing chamber based on Parylene coating and manufacturing method
CN116031101A
Vacuum arc extinguishing chamber
CN205609432U
Electric component unit
JP2020038919A
